The Intersection of Premenstrual Syndrome (PMS) and Mood Disorders: A Narrative Review - Makieła, Michalina; Dudek, Stanisław; Koziak , Weronika; Bętkowska, Aleksandra; Kornacka, Agata; Szostak, Kamila; Tomaka, Rafał; Dudek, Wojciech; Byra, Anna; Makieła, Marta (Quality in Sport, 2025)
Premenstrual Syndrome (PMS) encompasses a range of physical, emotional, and behavioral symptoms occurring cyclically during the luteal phase of the menstrual cycle. Mood disorders such as depression and anxiety often overlap with PMS, suggesting shared pathophysiological mechanisms. This narrative review explores the hormonal, neurochemical, psychosocial, and cultural factors contributing to the comorbidity of PMS and mood disorders. Understanding these interactions can guide effective diagnostic approaches and individualized treatment strategies.